Pembuktian Tindak Pidana Lingkungan Hidup Pembakaran Lahan Secara Berlanjut - Hudoyo, Ardhi Wikanto; Yulianti, S,H., M.H, Sri Wahyuningsih (Verstek, 2017)
This research aims is to determine the suitability of proof in environmental crime with article 96 of Law No. 32 of 2009 on the Protection and Management of the Environment and Article 184 paragraph (1) letter b of the Criminal Procedure Code, this is a normative law research or commonly called the doctrinal legal research done by researching library materials or secondary data consists of primary legal materials, secondary law and tertiary legal materials. Primary legal materials consist of legislation, notes the official records, the minutes in the making of legislation and the decision of the judge's decision.       As for the secondary law in the form of all the publicity about the law which is not an official document. The results of the research explaining that the Power of the evidence in the Supreme Court decision No. 131 / Pid.B / 2013 / PN.MBO dated July 15, 2014 in accordance with the provisions of article 96 of Law No. 32 of 2009 on the Protection and Management of the Environment and Article 184 paragraph ( 1) b Criminal Code because the evidence presented is not considered by the panel of judges that includes expert testimony and other evidence. So the judges gave fines to the defendant for the sanction.        Keywords: Evidence, Environmental Criminal